Navigating in harmony: Investigating spatial correlations between cetacean distribution and marine traffic in the Santos Basin, Brazil - Pratezi, Murilo Rainha [UNESP]; Rollo, Mario Manoel [UNESP] (Elsevier, 2024)
Cetaceans inhabit oceans worldwide, coexisting amidst the growing intensity of human activities in the aquatic environment, particularly motorized vessel traffic. Understanding spatial correlations is essential for devising appropriate responses to these impacts. Hence, this project delved into the spatial relationship between cetacean distribution and marine traffic activities in the Santos Basin, Brazil. Data from two different databases were collected: one detailing cetacean distribution and the other to documenting various types of marine traffic in general. A total of 2352 cetacean records and 718777 vessel records were obtained. Subsequently, Structural Similarity analyses were carried out to identify niche overlap, yielding a result of 0.88. Addition, analysis utilizing the Nearest Neighbor method and Kernel density were employed, to pinpoint overlapping records of marine traffic with cetaceans, generating heat maps. These findings facilitated the identification of the areas where marine traffic intersects with cetacean habitats, leading to the proposal of both mandatory and voluntary conservation strategies. Key recommendations include speed reduction and voluntary exclusion zones. It is anticipated that the implementation of these strategies in the study area will aid in the conservation of cetaceans and the broader biodiversity of Brazilian Marine Protected Areas.
Keywords: Cetaceans; Conservation strategies; Marine traffic; Niche overlap; Santos basin; Vessels